2010
DOI: 10.3390/mi1010019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Floor-grooved Micromixers using Concentration-channel Length Profiles

Abstract: Abstract:We evaluated the dynamic micromixing performances in slanted groove micromixers (SGM) and staggered herringbone micromixers (SHM) and quantitatively compared their differences using concentration vs. channel length profiles obtained from numerical stimulations. It is found that faster and finer mixing took place in the SHM and the chaotic mixing was more effective at locations closer to the grooves; in comparison, slower and coarser mixing occurred throughout the whole channel of the SGM. Subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…The geometries that have been incorporated into the microfluidic channels for promoting mixing efficiency include T-shaped microchannel, H-shaped micromixer, and grooved micromixer, etc. [7][8][9][10][11][12]. In particular, it has been demonstrated that a three-dimensional (3D) passive micromixer, which was designed basing on the Baker's transformation concept, can enable fast and efficient mixing even in the low-Reynolds-number condition [13].…”
Section: Introductionmentioning
confidence: 99%
“…The geometries that have been incorporated into the microfluidic channels for promoting mixing efficiency include T-shaped microchannel, H-shaped micromixer, and grooved micromixer, etc. [7][8][9][10][11][12]. In particular, it has been demonstrated that a three-dimensional (3D) passive micromixer, which was designed basing on the Baker's transformation concept, can enable fast and efficient mixing even in the low-Reynolds-number condition [13].…”
Section: Introductionmentioning
confidence: 99%
“…Good mixing efficiency is particularly important for fast complex chemical reactions where the reaction yields are strongly affected by mixing quality [1]. Degree of mixing can be achieved directly including experimentally [4] and numerically [18]; indirect methods include Poincare section analysis [19] and residence time distribution (RTD) evaluation [20].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrostatic potential is used to restructure a flow in a way wh ich results in faster mixing [1][2][3]. The mixing of microflu ids in a passive device is based on several main princip les: a) flow lamination, wh ich is used in basic T-mixers and Y-mixers [16][17][18][19][20][21], in mixers with different geometries: zig-zag, square-wave, rho mbic and the like [22][23], and in serial mu lti-stage and mu lti-layer mixers [24][25][26]); b) chaotic mixing by eddy format ion, stretching and folding [27][28][29][30][31][32][33]; c)split-and-reco mbine concepts (SAR) [34][35][36][37][38][39]. The mixing performance of passive mixers can be enhanced by extending the contact interface of flu ids and by improving the transverse components of flow movement, thus decreasing the length and duration of mixing [37].…”
Section: Introductionmentioning
confidence: 99%